Prediction of lymph node metastasis based on p53 and nm23-H1 expression in muscle invasive grade III transitional cell carcinoma of bladder - Park, Dong Soo; Lee, Young Tae; Lee, Jin Moo (Advances in experimental medicine and biology, 2003)
A surgically positive lymph node in invasive bladder cancer generally implies distant micrometastasis; thus, preoperative identification of lymph node status is important. Various antioncoproteins were evaluated for their accuracy in predicting lymph node metastasis. Fifty-seven subjects who had invasive, grade III transitional cell carcinoma at TURB, and then were confirmed to have stage T2, T3a, and T3b tumors after radical cystectomy from 1985 to 1994, were selected. Tissues acquired from transurethral resection were immunostained with tumor suppressor gene p53 (DO7 and PAb 1801) and antimetastatic gene nm23-H1 (NM301). Results of staining and pathological staging were compared with the status of lymph node metastasis. Expression of p53 was 42.1% (24/57) for DO7 and 22.8% (13/57) for PAb1801, with DO7 exhibiting superiority over PAb1801. Expression of nm23-H1 was seen in 50.9% (29/57) of cases. Combined analysis of p53 and nm23-H1 expression and nodal status (N stage) was not significant. However, pathological nodal status was statistically significantly correlated with pathological tumor (T) stage and p53 expression. A high risk of lymph node metastasis can be predicted when Grade III, muscle invasive tumor and p53 expression are seen from TURB specimens. Lymph node metastasis is correlated with the degree of invasion in Grade III muscle invasive tumors--especially in T3b tumors, where there is highest probability of node involvement.